2020
DOI: 10.1038/s41564-020-0762-5
|View full text |Cite|
|
Sign up to set email alerts
|

Reprogramming of host glutamine metabolism during Chlamydia trachomatis infection and its key role in peptidoglycan synthesis

Abstract: Obligate intracellular bacteria like Chlamydia trachomatis undergo a complex developmental cycle between infectious non-replicative (EBs) and non-infectious replicative (RBs) forms. EBs shortly after entering a host cell transform to RBs, a crucial process in infection, initiating chlamydial replication. As Chlamydia fail to replicate outside the host cell it is currently unknown how the replicative part of the developmental cycle is initiated. Here we show in a cell-free approach in axenic media that uptake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…In host cells, 2-oxoglutarate is an important intermediate in the mitochondrial TCA cycle, and glutamine is one of the important carbon sources to be catabolized to 2oxoglutarate (22)(23)(24). The first process of glutamine metabolism involves its conversion to glutamate by the mitochondrial matrix-localized phosphate-dependent glutaminase (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In host cells, 2-oxoglutarate is an important intermediate in the mitochondrial TCA cycle, and glutamine is one of the important carbon sources to be catabolized to 2oxoglutarate (22)(23)(24). The first process of glutamine metabolism involves its conversion to glutamate by the mitochondrial matrix-localized phosphate-dependent glutaminase (55).…”
Section: Discussionmentioning
confidence: 99%
“…In C. trachomatis infection, glutamine is rapidly utilized via glutaminolysis and the TCA cycle in order to generate glutamate and other metabolites such as 2-oxoglutarate (24). Since citrate synthase, aconitate hydratase, and isocitrate dehydrogenase are lacking in the chlamydial TCA cycle (22,23), C. trachomatis has to acquire host cell-derived 2-oxoglutarate using the porin PorB or glutamine/glutamate that can be catabolized to 2-oxoglutarate to fuel its own TCA cycle (23,24,56). Therefore, we suggest that mitochondrial activation via PTPs-STAT3 plays a key role in the generation of ATP as well as the enhancement of glutamine metabolism to compensate for the truncated chlamydial TCA cycle in productive C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is an important regulator of host cell metabolism and is indispensable for chlamydial acute infection and progeny formation 46 . Since Chlamydia obtain all nutrients from the host cell and it has been shown that several environmental conditions affecting host cell metabolism like iron and amino acid starvation also induce chlamydial persistence 51,52 , we investigated the role of c-Myc in chlamydial persistence.…”
Section: Resultsmentioning
confidence: 99%
“…Since Chlamydia obtain all nutrients from the host cell and it has been shown that several environmental conditions affecting host cell metabolism like iron and amino acid starvation also induce chlamydial persistence 51,52 , we investigated the role of c-Myc in chlamydial persistence. From our previous study, it was known that ablation of c-Myc expression interfered with chlamydial development and progeny formation 46 . To investigate if Chlamydia enter a persistence state in c-Myc depleted cells, we infected a HeLa 229 cell line with an anhydrotetracycline (AHT)-inducible short hairpin RNA (shRNA) for c-Myc in the absence and presence of the inducer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation